Exercício aeróbico crônico de natação promove alterações morfofuncionais em íleo de rato - Araujo, Layanne Cabral da Cunha (2014)
Abnormalities in intestinal contractile reactivity represent one of the pathophysiological processes that characterize intestinal colic, diarrhea and constipation. Exercise is an activity that affects all organs and tissues, resulting in many health benefits. E interferes with intestinal contractility in mice exercised on a treadmill, this decreasing contractility. The aim of this study was to evaluate the influence of chronic aerobic exercise swimming contractile reactivity, lipid peroxidation and morphology of the intestinal smooth muscle of rats. For this, we used Wistar rats (Rattus norvegicus) were divided into two groups, the sedentary group (SED), which was in contact with water for 2 minutes during the training of exercised rats. Exercised group (EX), who underwent a swim for an hour, being attached to the trunk of the animal a metal ring, corresponding to 3% of their body weight. The animals were divided into groups exercised that this procedure performed 5 days per week for 2 (EX2), 4 (EX4), 6 (EX6) or 8 (EX8) weeks. After the fifth day of training, the animals rested for 48 h. Then the animals were euthanized, ileum was removed and suspended in isolated organ baths and sinks to the isotonic contractions were recorded. All experimental protocols were previously approved by the Ethics Committee on Animal Use the CBiotec / UFPB (Protocol: 0907/13). Cumulative concentration-response curves to KCl were attenuated due to the exercise, as the values of Emax, which was reduced from 100% (SED) to 63.1 ± 3.9, 48.8 ± 3.8, 19.4 ± 1.8, 59.4 ± 2.8% in the groups exercised by 2, 4, 6 and 8 weeks, respectively. However, no significant difference in the power parameter. Similarly, the concentration-response curves to cumulative carbachol (CCh), were attenuated due to the exercise, as Emax values of 100% (SED) to 74.1 ± 5.4, 75.9 ± 5.2 62.9 ± 4.6% in the groups exercised by 2, 4 and 6 weeks, respectively. And EX8 group (E max = 89.7 ± 3.4%) was not significantly different from the SED group. However, the power of CCh contraction was not changed in relation to the SED group, but changed between groups EX2 (EC50 = 1.5 ± 0.5 x 10-6 M) EX8 (EC50 = 2.1 ± 0,4 x 10-7 M) EX6 (EC50 = 1.5 ± 0.3 x 10-6 M) EX8. The concentration of malondialdehyde (MDA), which indicates that lipid peroxidation was increased from 20.6 ± 3.6 mM/mL (SED) to 44.3 ± 4.4 mM/mL (EX4), but this was not peroxidation changed in EX6 (20.0 ± 3.6 mM/mL) and EX8 (17.2 ± 3.6 mM/mL) group. The total muscle layer (TML) was reduced from 75.5 ± 0.9 μm (SED) to 63.0 ± 1.3 μm (EX6), and no significant difference in the other exercise groups. The circular muscle layer (CML) was reduced from 50.9 ± 0.3 μm (SED) to 44.0 ± 1.8, 43.5 ± 1.3, 35.5 ± 1.4 and 41.6 ± 0.6 μm in groups trained for 2, 4, 6 and 8 weeks, respectively. Already the longitudinal muscle layer (LML) was increased from 21.6 ± 0.3 μm (SED) to 31.8 ± 1.0, 36.2 ± 2.5, 29.6 ± 1.8 and 30.8 ± 1.3 μm in groups trained by 2, 4, 6 and 8 weeks, respectively. According to the results, aerobic exercise alters the response of the ileum to KCl and CCh, reducing the amplitude of the intestinal contraction. Reduces oxidative damage, decreasing lipid peroxidation. And promotes changes in tissue level to establish an adaptation of the body to exercise. The data indicate a direct relationship between swimming exercise and reactivity of the intestinal smooth muscle of rat, which should be better studied and thus clarify the mechanisms involved and possible therapeutic implications.